The Effect of Environmental Issues on Customer’s Environmental Safety Pattern: An Experiential Text Analysis in the Literature - MS, Mahrinasari; PUJIYONO, S.; LAPIAN, Agnes L.Ch.; FIRMANSYAH, Arif; SAPTANTI, Noor; UNTARI, Dhian Tyas (Journal of Environmental Management and Tourism, 2022)
Rapid economic growth, especially in some developed and developing countries, has exacerbated the collapse of the environment. At this point, buying green products daily is considered an effective way to solve some of the excessive environmental problems. This study aims to investigate how the consumer's environmental protection purchase behavior affects corporate green marketing policies. To achieve this goal, current researchers have used qualitative textual analysis and collected data, including the current literature. As we focused on maximal validation, databases were mainly used to collect information from peer-reviewed sources. The result indicates that price sensitivity plays a detrimental role, especially in the correlation between green use objectives and environmental concerns. Also, the results reveal that environmental concern plays a fractional role, especially in environmental liability based on the intent of green use. The results of this study will be essential, especially how collaboration managers can establish their green marketing strategy with the aim of limiting price sensitivity, especially among customers. Finally, this study concludes that corporates must focus on diverting consumer attention to the price of green products. This can be done by highlighting some unique green products' qualities including environment-friendly, organic and low carbon productivity.